THE INVENTORY OF DIOXINS IN THE CHECHEN REPUBLIC - I. Y. Shahtamirov (Юг России: экология, развитие)
The article presents the results of calculations of the emission of dioxins in ambient air from stationary sources, transport and combustion processes on the territory of the Chechen Republic in different periods of industrial development. The main sources are the processes of uncontrolled burning of solid waste, fires and transport.